Supervisory Control of Full Converter Wind Generation Systems to Meet International Grid Codes - Mokui, Hasmina Tari (Curtin University, 2017)
This thesis proposes a new supervisory control scheme for full converter wind generators (FCWGs) in compliance with the latest international grid codes. Intermittent behaviour of wind turbines and maximum converter capacity are taken into account in determining the reactive power injection to the grid following severe disturbance. Detailed simulations show that the proposed controller can improve the fault-ride-through capability of FCWGs while also providing support to the network as required by the grid codes.